The use of aspirin for primary and secondary prevention in venous thromboembolism and other cardiovascular disorders. Issue 2 (February 2015) - Cohen, A.T.; Imfeld, S.; Markham, J.; Granziera, S.
Abstract Cardiovascular disease (CVD) includes a number of conditions such as myocardial infarction, coronary heart disease, stroke, and venous thromboembolism. CVD is a leading health problem worldwide and a major cause of mortality, morbidity, and disability; it is also associated with high healthcare costs. The incidence of CVD is predicted to increase in the forthcoming years, and thus it is crucial that physicians are aware of the benefits and limitations of the available therapies to ensure patients receive optimized treatment. Current clinical practice guidelines provide recommendations on the use of anticoagulants and antiplatelets for both the prevention and treatment of CVD. Aspirin is the most studied antiplatelet agent in this context. The benefits of aspirin are well documented and supported by data from robust clinical trials for CVD conditions, such as acute coronary syndrome and stroke prevention in patients with atrial fibrillation. However, the clinical benefits of aspirin are less clear for other conditions, namely for primary prevention of venous thromboembolism after major orthopaedic surgery, particularly in comparison with newer drugs such as the direct oral anticoagulants. This article provides an outline of the current guidelines and a critical assessment of the efficacy and safety data supporting the recommendations for the use of aspirin in the treatment and prevention of venous thromboembolism and other cardiovascular disorders.